Symmetry peculiarities of the intracrystalline fields layered semiconductor crystals (PbI₂)₍₁₋ₓ₎(BiI₃)ₓ - Barabash, O.I.; Vertegel, I.G.; Chesnokov, E.D.; Ovcharenko, O.I.; Ivanova, L.S. (Functional Materials, 2012)
The results of our study deal with the NQR spectra of ¹²⁷| at 77 K in mixed layered semiconductor crystals (PbI₂)₍₁₋ₓ₎(BiI₃)ₓ in a wide range of content Pbl₂ and Bil ₃ 0 < x < 1. It is shown that in the range of content 0 < x < 0.02 the crystal (Bil₃)₍₁₋ₓ₎(Pbl₂)ₓ has the properties of the impure crystal Pbl₂, which contains intralayer Bil₃ clusters, and in the range 0.8 < x < 1 it contains intralayer clusters Pbl2. Under the concentration x = 0.10 and x = 0.80 the crystal (PbI₂)₍₁₋ₓ₎(BiI₃)ₓ undergoes a phase transition and in the concentration range 0.1 < x < 0.8 there is a new crystal (PbI₂)₍₁₋ₓ₎(BiI₃)ₓ, in which groups of atoms Pbl₂ and Pbl₃ are intercalants fully or partially ordered in the crystal system.